Respuesta :
The equation of the new function is [tex]g(x)= cos4 x+1[/tex]
Explanation:
The Parent function is [tex]f(x)=cos x[/tex]
We need to determine the new function g(x) using the transformation by stretching the f(x) horizontally by a factor of 4 and shifting it 1 unit up.
The function transformation formula is given by
[tex]f(x)=a \cos b(x-c)+d[/tex]
Where a stretches the function vertically
b compresses or stretches it horizontally,
c shifts the function left or right
d shifts the function up or down
Since, it is given that the function stretches horizontally by a factor of 4 and shifting it 1 unit up.
Hence, [tex]b=4[/tex] and [tex]d=1[/tex]
Substituting these values in the formula, we have,
[tex]g(x)=cos4x+1[/tex]
Thus, the equation of the new function is [tex]g(x)= cos4 x+1[/tex]
The transformed function will be:
g(x) = cos(x/4) + 1.
How to get the equation of the transformed function?
First, we need to describe the two transformations used here, these are:
Horizontal stretch:
For a given function f(x), an horizontal stretch of scale factor k is written as:
g(x) = f(x/k)
Vertical shift:
For a given function f(x), a vertical shift of N unis is written as:
g(x) = f(x) + N
- If N is positive, the shift is upwards.
- If N is negative, the shift is downwards.
Here we have:
"... stretching it horizontally by a factor of 4 and shifting it 1 unit up."
Then:
g(x) = f(x/4) + 1
By replacing f(x) we get:
g(x) = cos(x/4) + 1.
If you want to learn more about transformations, you can read:
https://brainly.com/question/4289712